Antioxidant Properties and Transepithelial Transportation of Di‐/tripeptides Derived from Simulated Gastrointestinal Digestion of Pig Blood Cells Hydrolysates. Issue 3 (30th April 2020) - Ni, Xiaojun; Zhai, Zhenya; Xin, Zhongquan; Tan, Chengquan; Chen, Yiliang; Deng, Jinping; Liao, Pinfeng; Zhang, Limeng; Xiao, Zaili; Deng, Baichuan
Abstract : Pig blood is an important by‐product of the meat industry, which has not been fully utilized. In this study, Pig Blood Cells (PBC) were hydrolyzed by Alcalase and followed with simulated Gastrointestinal (GI) digestion to generate bioactive peptides. The antioxidant properties and the intestinal epithelial cells permeabilities of di‐/tripeptides from PBC Hydrolysates (PBCH) were investigated. PBCH showed higher 1, 1‐diphenyl‐2‐picrylhydrazy and 2, 2′‐Azino‐bis(3‐ethylbenzothiazoline‐6‐sulphonic acid) radical scavenging activities than PBC, although the activities were weakened by GI digestion. Besides, both PBCH and GI digested PBCH (PBCH‐GI) significantly improved cell viability and suppressed the production of reactive oxygen species under oxidative stress conditions in Caco‐2 cells. By using ultra performance liquid chromatography–orbitraptandem–mass spectrometry (UPLC–Orbitrap–MS/MS) technique, 5, 144, and 150 di‐/tripeptides sequences were characterized in the PBC, PBCH and PBCH‐GI groups, respectively. The transepithelial transportation revealed that the permeability of di‐/tripeptides through intestinal epithelial cells varied from 0.48% to 10.80%, and the peptides SDL, GDL, KF, FE exhibit high permeability values of 10.80%, 10.62%, 8.79% and 7.54%, respectively. These results indicate that PBCH has strong antioxidant properties and contains absorbable di‐/tripeptides, which is promising for functional food additive. GRAPHICAL ABSTRACT: